2013
DOI: 10.1149/05027.0143ecst
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Vapor on Sulfur Distribution Within La0.6Sr0.4Co0.2Fe0.8O3 Cathode

Abstract: Effect of water vapor on the sulfur poisoning of LSCF6428 cathode were investigated by comparison in performance and impedance spectroscopy of LSCF6428/10GDC cells, which were tested at 1073 K (800 o C) for 100 h under two conditions: (a) 1 ppm SO 2 with dry air and (b) 1 ppm SO 2 with 1.2% humidified air. Results of performance degradation revealed that degradation speed is accelerated about 10 times in the presence of water vapor. Detailed SEM analyses show that the amount of formed SrSO 4 during the same op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…1,2 Many studies have investigated the sulfur poisoning behavior of cathode materials such as La 1−x Sr x CoO 3−δ (LSC), La 1−x Sr x MnO 3−δ (LSM), La 1−x Sr x Co 0.2 Fe 0.8 O 3−δ (LSCF) and tried to clarify their degradation mechanisms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For LSM, essentially no cathode performance degradation occurs. Secondary phase formation, if any, can take place at any area of the cathode showing no selectivity near the triple-phase boundary (TPB) at the electrode/electrolyte interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Many studies have investigated the sulfur poisoning behavior of cathode materials such as La 1−x Sr x CoO 3−δ (LSC), La 1−x Sr x MnO 3−δ (LSM), La 1−x Sr x Co 0.2 Fe 0.8 O 3−δ (LSCF) and tried to clarify their degradation mechanisms. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For LSM, essentially no cathode performance degradation occurs. Secondary phase formation, if any, can take place at any area of the cathode showing no selectivity near the triple-phase boundary (TPB) at the electrode/electrolyte interfaces.…”
mentioning
confidence: 99%
“…The sulfur poisoning effects on the LSCF cathode has been investigated in high concentrations of SO 2 (0.1, 1, 10, 100 ppm SO 2 in air). [6][7][8][9][10] It was found that SO 2 reacts with the Sr component in LSCF to form SrSO 4 , which leads to the performance degradation. With increasing sulfur concentration, faster degradation was observed.…”
mentioning
confidence: 99%
“…Researchers have also found that levels of sulfur at the ppb level in the form of SO 2 can cause serious performance degradation in cathodes 33 . This seems to be related to the surface strontium enrichment described above, with surface strontium forming SrSO 4 , likely triggering the local decomposition of the cathode material or reducing the strontium content in the bulk enough to reduce the conductivity 34 . Sulfur tolerant cathode materials need to be developed, as the current solution is a chemical sulfur scrubber, which inevitably increases cost and decreases efficiency and power density.…”
Section: Lifetime and Degradationmentioning
confidence: 98%
“…Our group has investigated the degradation behavior of LSCF cathodes induced by SO 2 containing air. It is observed that SO 2 induced degradation is affected by the SO 2 concentration in air [4], the Sr content in LSCF cathode [5], the flow rate of air [6], and the humidity of air [7]. In the present study, we mainly focused on the temperature dependence of degradation behavior of (La 0.6 Sr 0.4 )(Co 0.2 Fe 0.8 )O 3 (LSCF6428) by SO 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Degradation of LSCF cathodes is induced by impurities in air. One of the most recognized impurities is sulfur dioxide (SO 2 ) [1][2][3][4][5][6][7][8][9][10]. Our group has investigated the degradation behavior of LSCF cathodes induced by SO 2 containing air.…”
Section: Introductionmentioning
confidence: 99%